PENGARUH KNOWLEDGE MANAGEMENT PRACTICES TERHADAP ORGANIZATIONAL PERFORMANCE DI PERUSAHAAN RINTISAN DARING INFLUX. - Delinna Delinna; Agus Gunawan; Angela Caroline; Yoke Pribadi Kornarius (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
COVID-19 pandemic has changed the work pattern and behaviour across the world. One of them is the remote working setup that has been adopted by many companies, especially start-ups. Technology helps people work together even they’re located at a difference place and time. However, there’s a challenge in remote work, which is managing knowledge to improve organizational performance. This explanatory research aims to know the degree of knowledge management practices’ (KMP) influence to organizational performance (OP). This degree of influence is supported by human resources, process and structure, technology, and management encouragement. Sampling technique used here is purposive sampling where the number of samples are 32 respondents. The result of this research indicates strong influence of KMP to OP that is equal to 0,560. Besides, KMP influences OP positively under R-Square value which is 0,314. Knowledge sharing and dissemination (KMP 3) is the main factor in supporting the organizational performance, through platform enablement and employee collaboration in knowledge sharing. On its implementation, the company should retain this good practice by communication the KMP process and procedures, then evaluate it for greater advantages both for the company and the clients.